The Registration Of The Deed Of Grant Of Dependent Rights Electronically Without The Granting Of Power Of Attorney To Ppat By Creditors Is Linked To The Principle Of Legal Certainty - Julya, Monique Salcha; Mulyati, Etty; Nurhayati, Elis (UNIVERSITAS PAKUAN, 2025)
ABSTRACTRegulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 5 of 2020 concerning Electronically Integrated Mortgage Rights Services (Permen HT-el) regulates the electronic registration of Mortgage Rights, where the application for registration must be made by the creditor without being authorized by the Land Deed Official (PPAT) as in the conventional Mortgage Rights system. Electronic registration of Mortgage Rights will create legal certainty for the holder of the Mortgage Rights in the form of an Electronic Mortgage Rights Certificate. In practice, there are still creditors who have not or do not register electronic Mortgage Rights at all, causing legal certainty not to be guaranteed because the Mortgage Rights are not born. This study aims to determine and analyze the legal certainty of electronic registration of mortgage rights, where the application for registration is the obligation of the creditor. The research method used is normative juridical, namely research on principles, norms and legal rules. The research specification uses descriptive analytical method, namely by providing an explanation of the facts contained in the research object comprehensively, systematically, accurately and factually and then correlating it with relevant legal theories. The results show that without an application for electronic registration of Mortgage Rights by the creditor, the Mortgage Rights are considered to have never existed. The banking party as the creditor must increase human resources who are ready and there must be additional human resources from the Bank as a creditor specifically to register electronic Mortgage Rights. Keywords: APHT, Electronic Mortgage Rights, Legal Certainty.